DISTRIBUTION AND ECOLOGICAL CHARACTERISTICS OF HYALOMMA IXODID TICKS IN THE ECOSYSTEMS OF THE STAVROPOL REGION - V. I. Trukhachev; Yu. M. Tokhov; S. N. Lutsuk; A. A. Dylev; V. P. Tolokonnikov; Yu. V. Dyachenko (Юг России: экология, развитие)
Aim. To determine the characteristics of the modern dissemination, distribution and seasonal activity of Hyalomma ixodid ticks in the Stavropol region.Methods. The study of the spread of Ixodes Hyalomma ticks was conducted in all administrative districts of the Stavropol Territory in the period of 2000-2015. Collection of ixodid ticks in natural habitats, home to wild mammals and birds, was carried out according to conventional techniques.Results. Hyalomma marginatum is a two-host tick. In the region, H. marginatum of an adult stage becomes active in early spring (late March - early April); appearance of the larvae is observed in early July; the nymphs in the third decade of July. The peculiarity of biological development of H. scupense is the activation of adult species in the cold season (winter); development is only of one-host cycle. The peak number of ticks of an adult stage in cattle falls on the last days of January and February.Conclusion. Hyalomma ixodid ticks in the Stavropol region are distributed mosaicly, with the dominance of some species depending on climatic and landscape-geographical features of the territories they inhabit. The dominant species are H. marginatum and H. scupense, but H. anatolicum tick species occur sporadically in the east region.